Knowledge Solutions Tools, Methods, and Approaches to Drive Organizational Performance - Serrat, Olivier (Springer Singapore : Imprint: Springer, 2017)
This book is open access under a CC BY-NC 3.0 IGO license. This book comprehensively covers topics in knowledge management and competence in strategy development, management techniques, collaboration mechanisms, knowledge sharing and learning, as well as knowledge capture and storage. Presented in accessible “chunks,” it includes more than 120 topics that are essential to high-performance organizations. The extensive use of quotes by respected experts juxtaposed with relevant research to counterpoint or lend weight to key concepts; “cheat sheets” that simplify access and reference to individual articles; as well as the grouping of many of these topics under recurrent themes make this book unique. In addition, it provides scalable tried-and-tested tools, method and approaches for improved organizational effectiveness. The research included is particularly useful to knowledge workers engaged in executive leadership; research, analysis and advice; and corporate management and administration. It is a valuable resource for those working in the public, private and third sectors, both in industrialized and developing countries.